2005
DOI: 10.1186/1471-2334-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Effective antiprotease-antibiotic treatment of experimental anthrax

Abstract: Background: Inhalation anthrax is characterized by a systemic spread of the challenge agent, Bacillus anthracis. It causes severe damage, including multiple hemorrhagic lesions, to host tissues and organs. It is widely believed that anthrax lethal toxin secreted by proliferating bacteria is a major cause of death, however, the pathology of intoxication in experimental animals is drastically different from that found during the infectious process. In order to close a gap between our understanding of anthrax mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…There is strong evidence that proteases contribute substantially to anthrax as well, and the InhA1 protease, which is suggested from the findings of the present study to degrade hemoglobin, is involved in a number of pathogenic properties for Bacillus species. Popov and colleagues (57) found that protease inhibitors showed a synergistic protective effect when administered with antibiotics in mice given a lethal dose of B. anthracis, suggesting that proteolytic activity contributes to the onset of anthrax. Indeed, mice infected with a B. anthracis strain lacking inhA1 survived longer than their wild-type-infected counterparts, a property potentially related to the fact that many fewer bacilli penetrate the bloodbrain barrier and infect the brain (58).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that proteases contribute substantially to anthrax as well, and the InhA1 protease, which is suggested from the findings of the present study to degrade hemoglobin, is involved in a number of pathogenic properties for Bacillus species. Popov and colleagues (57) found that protease inhibitors showed a synergistic protective effect when administered with antibiotics in mice given a lethal dose of B. anthracis, suggesting that proteolytic activity contributes to the onset of anthrax. Indeed, mice infected with a B. anthracis strain lacking inhA1 survived longer than their wild-type-infected counterparts, a property potentially related to the fact that many fewer bacilli penetrate the bloodbrain barrier and infect the brain (58).…”
Section: Discussionmentioning
confidence: 99%
“…anthracis produces, in addition to the major virulence factors, at least four separate proteases that promote host tissue degradation to break down barriers to bacterial dissemination (59). These proteases break down gelatin, casein, fibronectin, laminin, and collagen.…”
Section: Dissemination Factorsmentioning
confidence: 99%
“…It has been suggested that the evolutionary inactivation of the PlcR regulon in B. anthracis was due to incompatibility with the AtxAcontrolled regulon and reflects the fact that the PlcR target genes are not essential for anthrax pathogenicity (96). Several studies have postulated that secreted proteases, other than those belonging to the silenced PlcR regulon, are responsible for some clinical manifestations of anthrax (1,9,117,140). Such proteases could damage host tissues, interfere with immune effectors of the host, and/or provide nutrients for bacterial survival (103).…”
mentioning
confidence: 99%